Nonsteroidal anti-inflammatory drugs act as endocrine disruptors in Astyanax lacustris (Teleostei: Characidae) reproduction: An ex vivo approach - Branco, Giovana Souza [UNESP]; Moreira, Renata Guimarães; Borella, Maria Inês; Camargo, Marília de Paiva; Muñoz-Peñuela, Marcela; Gomes, Aline Dal'Olio; Tolussi, Carlos Eduardo (Elsevier, 2021)
Pharmaceutical products can act as endocrine-disrupting compounds (EDCs), affecting the physiological processes of animals, such as development or reproduction. This study aimed to investigate the influence of different concentrations of nonsteroidal anti-inflammatory drugs (NSAIDs) diclofenac (DCF) and ibuprofen (IBU) alone and mixed (MIX) on gonadotropin gene expression and gonadal steroid release using Astyanax lacustris pituitary and testes explant systems, respectively. The explant organs were maintained for 12 h in Leibovitz (L-15) medium supplemented with 0, 0.1, 1, 10, 100, and 1000 ng L−1 of DCF, IBU, and MIX (ratio 1:1 of the same concentrations of DCF and IBU alone) and gonadotropin releasing-hormone (cGnRH2) stimulation in pituitary explants and human chorionic gonadotropin (hCG) stimulation in testes explants. The pituitary glands and the media from the testicular explants were collected for gene expression analysis including the β subunit of the follicle-stimulating hormone (fshβ) and luteinizing hormone (lhβ) and secreted gonadal steroid concentration analysis, respectively. Both DCF and IBU (alone and mixed) decreased pituitary gene expression of fshβ and lhβ and this inhibitory effect was evident even at low concentrations. In the testes, DCF and IBU did not change the levels of estradiol, and both pharmaceuticals increased the release of 11-ketotestosterone at low doses, while only IBU decreased the levels of testosterone in all concentrations. IBU's inhibitory effect in the testes was not triggered by the mixture of the two drugs. These results suggest that NSAIDs, may interfere in fish reproduction by acting as EDCs, thereby negatively affecting A. lacustris spermatogenesis and maturation.
Keywords: Diclofenac; Gonadotropins; Ibuprofen; Reproduction; Steroids; Testes